VIBRATION CONTROL OF ICE-INDUCED LOADING ON JACKET PLATFORM BY USING STEEL RUBBER VIBRATION ISOLATOR - Bin Subari, Syamim Haikal (Universiti Teknologi PETRONAS, 2018)
The most common force that will be faced by the offshore platforms are environmental load, one of them is ice load. In icy environment ice load is a must to be taken as consideration because ice is one of the factor for fatigue failure to occur. Fatigue failure occurred due to the weakening of offshore platform’s joint when there are various load impacting on them. Moreover, as the ice hitting the offshore platform, the vibration from the ice will cause the fatigue failure to occur. To reduce or mitigate the ice force, a method had been proposed to determine if vibration from ice force can be reduced by using steel rubber isolator. To determine if steel rubber isolator can reduce the ice force, model simulation has been run by using a commercial Software. The software will compare two different offshore platforms where the first platform contain steel rubber isolator and the second platform have no steel rubber isolator. Later the result analysis will be obtained and conclusion can be made if the steel rubber isolator can be proven to reduce the vibration due to ice force.